MODEL OF SENSITIVITY CATTLE TO MASTITIS ON THE BASIS OF LYMPHOCYTIC AND MOLECULAR GENETIC MARKERS - Т. М. Супрович; М. П. Супрович; Л. В. Строяновська; І. О. Чорний (Подільський вісник: сільське господарство, техніка, економіка)
Mastitis of cows causes significant harm to dairy farming, a susceptibility to which is partly determined by genetic factors. Therefore, identifying the susceptibility or resistance of cows to mastitis at an early stage of postnatal ontogenesis has both practical and scientific importance. In this work, we examined a model grounded on the collegial use of lymphocyte antigens class I MHC cattle and DNA markers based on alleles BoLA-DRB3 gene to identify the sensitivity of heifers to mastitis to their use in a milking herd. On the data of testing of 649 cows of the Ukrainian black-and-white breed, the antigens of histocompatibility were revealed, and the statusmetric model facilitated determining the integral estimation of sensitiveness (Z) to mastitis was constructed. The greater the positive Z value, the higher the predicted resistance to mastitis and vice versa. The model yields 69.2% correct mastitis susceptibility decisions based on 17 class I antigens (antigens W2, W6, W31, W14, W19, W15, A9, A12, A13 and A24 indicate susceptibility and W10, A1, A3, A6, A16, A17 and A22 – indicate resistance to the disease). Some exon 2 alleles of the BoLA-DRB3 gene were found to be associated with mastitis. For 162 cows from the preliminary sample DRB3.2*18, *24, *26 and *48 alleles characterize susceptibility to mastitis, and BoLA-DRB3.2*08, *13 and *22 – characterize resistance to the disease. A comparative analysis of the association of lymphocyte and DNA-markers was performed by comparing the diagnosis, status score, and the presence of associated alleles in the genotype. Two of the four possible variants unambiguously indicate the immune status of the cow: – diagnosis and integral score (by sign) coincide, and there is an allele in the genotype that coincides with the established diagnosis (65,7%); – diagnosis and integral score sign do not coincide, and there is a DNA marker in the genotype that coincides with the immune status of the animal by Z (13,3%). For 83 animals out of 105 in which DNA markers were detected, the immune status established by the statusmetric model was confirmed, for a total of 79%. The accuracy in predicting the susceptibility of cows to mastitis increased by 9.8%. Following the obtained results, the model for predicting sensitivity of heifers of Ukrainian black-and-white breed to mastitis at the stage of early postembryonic ontogenesis has been proposed. The model is universal and can be applied to different cattle breeds after appropriate research.